Chemical Recycling of Waste Polypropylene via Thermocatalytic Pyrolysis over HZSM-5 Catalysts - Inayat, Amer; Inayat, Alexandra; Schwieger, Wilhelm; Klemencova, Katerina; Lestinsky, Pavel (Chemical Engineering & Technology, 2023)
The present work deals with the chemical recycling of waste polypropylene via thermocatalytic pyrolysis over HZSM-5 zeolite catalysts. The main aim was to systematically investigate the influence of reactor configuration, zeolite acidity, polypropylene wastes, obtained from different sources, as well as catalyst regeneration on the product distribution. It was demonstrated that the reactor configuration and the acid site density of HZSM-5 catalysts strongly influence the product yields and distributions. The different types of polypropylene waste, on the other hand, showed a comparatively small yet noticeable effect on the product distribution. Moreover, it was demonstrated that the HZSM-5 catalysts exhibit good regeneration capacity during regeneration-reaction cycles.
CRIS-Team WoS Importer:2023-04-14